RIGHTS TO EDUCATION: HOMESCHOOLING IN INDONESIA - Permanasari, Ai (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Children have the right to get a good education according to the best interests of the child. Formal schools have various obstacles that cause the right to education to be not optimally fulfilled. For this reason, alternatives are needed to fulfill children's right to education. Homeschooling is an informal education path that is increasingly being chosen by parents. Even though the legality of homeschooling has been recognized equally with formal education, attention must be paid to the fulfillment of children's right to education in homeschooling. This is because homeschooling is the realm of parents which is almost absolute, and then because the system of learning and supervision is different from other educational pathways, so further research is needed on how homeschooling is regulated within the national framework, and whether homeschooling can fulfill children's right to education. In this article it will be found that supervision of homeschooling in Indonesia is still weak. Supervision in homeschooling in this case is only supervision from parents and educators. The absence of technical guidelines and implementation instructions for Regulation of the Minister of Education and Culture Number 129 of 2014 makes supervision of homeschooling in Indonesia unclear and this leads to potential violations of children's rights to education where there is no guarantee of the quality of education for children who are homeschooling, as well as the potential for possible exposure to radicalism, abuse and exploitation of children.